2014
DOI: 10.3389/fneur.2014.00053
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Dexterity as the Dynamical Regulation of Instabilities: Comparisons Across Gender, Age, and Disease

Abstract: Dexterous manipulation depends on using the fingertips to stabilize unstable objects. The Strength–Dexterity paradigm consists of asking subjects to compress a slender and compliant spring prone to buckling. The maximal level of compression [requiring low fingertip forces <300 grams force (gf)] quantifies the neural control capability to dynamically regulate fingertip force vectors and motions for a dynamic manipulation task. We found that finger dexterity is significantly affected by age (p = 0.017) and gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
69
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(80 citation statements)
references
References 70 publications
11
69
0
Order By: Relevance
“…Mosier et al (2011) found that the level of instability achieved showed a strong association with increase in the BOLD signal in basal ganglia and in the cerebellar-parietal network. Lawrence et al (2014) showed that spinal circuits are likely heavily involved in the regulation of instabilities during spring compressions. In the present study these findings are extended: activity was revealed in the basal ganglia, both with and without tactile input.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…Mosier et al (2011) found that the level of instability achieved showed a strong association with increase in the BOLD signal in basal ganglia and in the cerebellar-parietal network. Lawrence et al (2014) showed that spinal circuits are likely heavily involved in the regulation of instabilities during spring compressions. In the present study these findings are extended: activity was revealed in the basal ganglia, both with and without tactile input.…”
Section: 4mentioning
confidence: 99%
“…According to a hierarchical view of motor control (Kawato et al, 1987;Loeb et al, 1999;Konen and Kastner, 2008) dexterous manipulation capabilities, such as the compression of an unstable spring prone to buckling, are likely not exclusively controlled Q7 by the neo-and somatosensory cortices (Lawrence et al, 2014;Lemon, 1993;Schieber, 2011) but involve also subcortical and spinal structures (Lawrence et al, 2014). Even if we presume a limited role of the spinal cord in movement generation in humans, the spinal cord can certainly shape the motor commands coming from supraspinal structures by gating, inhibiting, or disinhibiting the behavior of spinal circuitry (Pierrot-Deseilligny and Burke, 2005).…”
Section: 4mentioning
confidence: 99%
“…It was originally developed for fingers[3, 5, 42], and then adapted into a lower extremity dexterity test to quantify the dynamical ability to stabilize unstable foot-ground interactions[19, 23]. We have previously reported sex differences in this leg version in young soccer players[22] and across the lifespan[19] and proposed that may contribute to the disproportionate higher number of non-contact ACL injuries in female athletes compared to males. As such, it is important to understand the influence of athletic ability—likely, in part, a result of long-term exposure to athletic training regimens—on sensorimotor control for leg dexterity.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional measures of leg function during whole-body activity are confounded by the contribution of the functional domains of strength and/or limb coordination—let alone vestibular function, visual acuity, posture control, risk aversion, etc. However, we have shown that different versions of the Valero-Cuevas dexterity test quantify the functional domain of sensorimotor processing, as distinct from the functional domains of strength and limb coordination, in fingers[3, 5, 19, 41] and legs[18] (Figure 1). This simple, yet reliable, test requires participants to compress a slender spring prone to buckling at low forces to a maximal steady state level[23, 41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation